Penerapan Lean Logistics dengan Metode Six Sigma untuk Meningkatkan Kualitas Distribusi Telur Asin - Rajendra, Shafa Nandana Arva; Purnawan, Purnawan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
UMKM TA is a business that is engaged in processing and selling salted egg products. UMKM TA is experiencing problems in the salted egg distribution process in its operations. This study uses the Lean Six Sigma method with the DMAIC stage to overcome this. This study uses the Lean Six Sigma method with using several tools such as the SIPOC diagram, Fishbone diagram, and 5W + 1H. The result of the sigma value in this study is 2.224. Problems are caused by machine, human, method, and material factors. Implementation of improvements is done with what, where, when, why, who¸ and how questions. In maintaining the implementation of these improvements, a control stage is carried out by implementing the distribution SOP and measuring distribution performance.